Caracterización del perfil de egreso de los profesionales de la Universidad Técnica Estatal de Quevedo - Chévez Castro, María Isabel (2024)
This project analyzed the gap that exists between the graduation profile of the students of the Software and Telematics careers of the State Technical University of Quevedo and the professional profile demanded by the companies in the Hiring Room. For this purpose, descriptive statistics techniques, text mining and topic modalization with Dirichlet Latent Localization were applied to find topics and keywords within texts. Once both profiles are described, it is required to analyze the gap in terms of the ability of graduate students to fill these demanded vacancies with the help of text mining. For the analysis of the graduation profile of the Software and Telematics careers, the Latent Dirichlet Localization (LDA) method was applied to the curricula, graduation profile and specific competencies with which students graduate. In this way it was possible to know to what extent students are qualified to fill a vacancy in the labor market. For the analysis of the professional profile demanded in Hiring Room, the data was obtained through the Web Scraping technique or scraping of the Web to the ads in Hiring Room, the sample to consider was 356 job ads this year in Ecuador, once obtained the data, text mining techniques were applied and text preprocessing to facilitate the application of Latent Location Dirichlet, finally describing the professional profile.